13
$\begingroup$

I would like to show that:

$$ \sum_{n=1}^{\infty} \arctan \left( \frac{2}{n^2} \right) =\frac{3\pi}{4}$$

We have:

$$ \sum_{n=1}^N \arctan \left( \frac{2}{n^2} \right) =\sum_{n=1}^N \arctan (n+1)-\arctan(n-1) =-\frac{\pi}{4}+\arctan N+\arctan(N+1)\rightarrow \frac{3\pi}{4}$$

Do you agree with my proof?

$\endgroup$
  • 4
    $\begingroup$ You have to write $\sum_{n=1}^N \left (\arctan (n+1)-\arctan(n-1)\right )$ $\endgroup$ – student Nov 24 '12 at 16:45
6
$\begingroup$

Everything is fine with this proof.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Thanks, that's all I wanted to hear! $\endgroup$ – Chon Nov 24 '12 at 17:07

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.